COMPARISON OF SELECTIVE MEDIA FOR THE DETECTION OF ESCHERICHIA COLI IN WATER - M.K. Sharifi-Yazdi; C.Azimi (Tehran University of Medical Sciences, 1999)
The performance of selective media LTB, (leauryl tryptose broth), MMGM (minerals modified glutamate medium), BGBB (brilliant green bile broth), for the detection of E.coli in water in water, were compared and the following result were obtained: The MMGM found to be unsuitable as confirmatory medium for the detection of E.coli at 44 C, due to the occurrence of an unacceptable number of the false-negative and false-positive results. The comparison of the two confirmatory medium LTB, BGBB for the confirmation of E.coli at 44 C, it was found that LTB was less inhibitory than BGBB for the recovery of E.coli in mixed populations. The occurrence of a higher number of false-negatives in BGBB is a more serious disadvantage since it would lead to an underestimate of the actual number of E.coli. Therefore, the results of this study showed that LTB is a more suitable confirmatory medium than BGBB.